2006
DOI: 10.1002/cvde.200506368
|View full text |Cite
|
Sign up to set email alerts
|

The CVD of Nanocomposites Fabricated via Ultrasonic Atomization

Abstract: Composite thin films have been created by a novel technique employing ultrasonic atomization to introduce the particles into the vacuum chamber during plasma-enhanced (PE) deposition of a matrix material. Co-deposition has been confirmed by both fluorescence microscopy and FTIR analysis. Particle deposition has been explored in the context of solvent properties as well as reactor conditions, and the results have been examined in the framework of the calculated mass drying rate and droplet lifetime. This techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Profili et al [8] implemented a one-step approach for the deposition of ZnO-SiO2 NC coatings on wood by the atomization of a stable suspension of ZnO dispersed in hexamethyldisiloxane (HMDSO) in an atmospheric pressure dielectric barrier discharge (DBD). Ross et al [9] elaborated composite films using an ultrasonic atomizer and a PECVD system using Tetraethoxysilane (TEOS) as a matrix precursor and polystyrene nanoparticles with a mean size of 96 nm. The pressure in the specific system was varied between 100 and 500 mTorr.…”
Section: Introductionmentioning
confidence: 99%
“…Profili et al [8] implemented a one-step approach for the deposition of ZnO-SiO2 NC coatings on wood by the atomization of a stable suspension of ZnO dispersed in hexamethyldisiloxane (HMDSO) in an atmospheric pressure dielectric barrier discharge (DBD). Ross et al [9] elaborated composite films using an ultrasonic atomizer and a PECVD system using Tetraethoxysilane (TEOS) as a matrix precursor and polystyrene nanoparticles with a mean size of 96 nm. The pressure in the specific system was varied between 100 and 500 mTorr.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that incorporation of IF-WS 2 nanoparticles into coatings would offer considerable improvements on tribological performance [13,14] and adjust hydrophobic/hydrophilic behavior of the coating surface [15]. Recently, aerosol-assisted chemical vapor deposition (AACVD) has been adapted to synthesize inorganic nanocomposite coatings from the dispersion or colloid of nanoparticles [16,17]. We have also incorporated IF-WS 2 nanoparticles into Cr 2 O 3 coating using AACVD [18].…”
Section: Introductionmentioning
confidence: 99%
“…The first report using a low-pressure plasma system, aiming at the simultaneous injection of the NPs in a solution and the injection of the matrix precursor using the PECVD technique, has been proposed by Ross et Gleason [126] in 2006. These authors report that the atomization of the solution is accomplished by a 40 kHz ultrasonic atomizer (Sonics and Materials, model VC134-AT with custom probe) located at the top of the reactor.…”
Section: Low-pressure-based Systemsmentioning
confidence: 99%